BUDAYA ORGANISASI DAN KINERJA PEGAWAI - Novita Hari Widyanti (Universitas Riau, 2015)
Organizational Culture and Performance Officer. The purpose of this study was to determine the influence of organizational culture on employee performance. The research location is the Riau Provincial Inspectorate. The study population was the entire staff of 96 people. All the population sampled or census. Collecting data using questionnaires, interviews and observation. The results showed that organizational culture has positive influence on the performance of employees amounted to 0.411 with 5% significance. But the contribution of organizational culture on employee performance is only 14.2% and the remaining 85.8% is influenced by other factors.